IDENTIFICATION AND PATHOGENICITY TEST OF SOME BACTERIA ISOLATED FROM WILD AND FARMED SPINY LOBSTER Panulirus homarus - Sudewi Sudewi; Zeny Widiastuti; Indah Mastuti; Ketut Mahardika (Research Center for Biology-Indonesian Institute of Sciences, 2019)
The bacterial populations in the farming of spiny lobster could have either beneficial or harmful effects depending on the prevailing conditions. We designed this study to identify and to perform a pathogenicity test of some bacteria isolated from wild and farmed spiny lobsters Panulirus homarus. The adult farmed lobsters were obtained from Pangandaran and Lombok coastal areas, while the wild lobsters were collected from Lombok, with five lobsters for each location. The bacteria were isolated from the midgut, gill, hepatopancreas, and muscle tissues of the lobsters. The identification of the bacteria was carried out by molecular methods. Pathogenicity test was performed by intramuscular injection of 0.1 ml bacterial suspensions at the density of 7×106cfu/ml into each three adult apparently healthy lobsters for every eight bacterial isolates. Our study identified six bacterial isolates that exhibited high homology of a nucleotide sequence with Shewanella algae, Bacillus firmus, Vibrio alginolyticus, Tenacibaculum lutimaris, Pseudomonas sp. and Vibrio sp., while two isolates were reminded unidentified due to low nucleotide similarities (< 97%). The pathogenicity test showed that there was no mortality of lobsters injected with those bacterial isolates. This may because the dose of injection was too low to induce bacterial infection particularly for Vibrio, or the bacteria were not pathogenic for lobster or even have the potency as probiotic bacteria.